2015
DOI: 10.18632/oncotarget.4014
|View full text |Cite
|
Sign up to set email alerts
|

EGFR blockade prevents glioma escape from BRAFV600E targeted therapy

Abstract: Mutational activation of BRAF (BRAFV600E) occurs in pediatric glioma and drives aberrant MAPK signaling independently of upstream cues. Targeted monotherapy against BRAFV600E displays efficacy in pre-clinical models of glioma, however xenograft tumors adapt rapidly and escape from the growth-inhibitory effects of BRAF-targeted therapy. Here, we show that intrinsic resistance to a BRAFV600E specific inhibitor stems, in part, from feedback activation of EGFR and downstream signaling pathways. BRAFV600E inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
5
29
0
Order By: Relevance
“…Nonetheless, our results shown that 2341 grafts adapt to Tr monotherapy, whereas combination treatment delayed acquired resistance (Figure 6A). Our data are consistent with those obtained by studying human BRAF V600E mutant glioma cell lines, which point to re-activation of MAPK pathway and increased AKT and EGFR signaling activity as a mechanisms of adaptation and resistance to BRAF V600E inhibition (Supplementary Figure S3) [21, 46]. These similarities suggest that our mouse model has clinical relevance.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, our results shown that 2341 grafts adapt to Tr monotherapy, whereas combination treatment delayed acquired resistance (Figure 6A). Our data are consistent with those obtained by studying human BRAF V600E mutant glioma cell lines, which point to re-activation of MAPK pathway and increased AKT and EGFR signaling activity as a mechanisms of adaptation and resistance to BRAF V600E inhibition (Supplementary Figure S3) [21, 46]. These similarities suggest that our mouse model has clinical relevance.…”
Section: Discussionsupporting
confidence: 89%
“…This includes mutations in PTEN as shown above, as well as RAS mutations and activation of receptor tyrosine kinase signaling (Luke and Hodi, 2012). Feedback activation of EGFR has specifically been suggested as an escape pathway in BRAF V600E CNS tumor cells (Yao et al, 2015). The above data suggest that autophagy inhibition is able to overcome BRAFi resistance in different tumor types, and that distinct mechanisms of resistance can be similarly targeted by this approach.…”
Section: Resultsmentioning
confidence: 99%
“…Feedback activation of EGFR, represents another mechanistically-distinct resistance mechanism that can provide an escape pathway in BRAF V600E CNS tumor cells (Yao et al, 2015). Therefore, we also developed cell lines with EGFR overexpression (EGFRoe) and evaluated their response to autophagy inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations